Searching for the Least Invasive Management of Pelvi-Ureteric Junction Obstruction in Children: A Critical Literature Review of Comparative Outcomes - Castagnetti, Marco; Iafrate, Massimo; Esposito, Ciro; Subramaniam, Ramnath (Frontiers in Pediatrics, 2020)
Introduction: To review the published evidence on the minimally invasive pyeloplasty techniques available currently with particular emphasis on the comparative data about the various minimally invasive alternatives to treat pelvic-ureteric junction obstruction and gauge if one should be favored under certain circumstances. Material and Methods: Non-systematic review of literature on open and minimally invasive pyeloplasty including various kinds of laparoscopic procedures, the robotic-assisted laparoscopic pyeloplasty, and endourological procedures. Results: Any particular minimally invasive pyeloplasty procedure seems feasible in experienced hands, irrespective of age including infants. Comparative data suggest that the robotic-assisted procedure has gained wider acceptance mainly because it is ergonomically more suited to surgeon’s well-being and facilitates advances skills with dexterity thanks to seven degrees of freedom. However, costs remain the major drawback of robotic surgery. In young children and infants, instead, open surgery can be performed via a relatively small incision and quicker timeframe. Conclusions: The best approach for pyeloplasty is still a matter of debate. The robotic approach has gained increasing acceptance over the last years with major advantages of the surgeon well-being and ergonomics and the ease of suturing. Evidence however may favor the use of open surgery in infancy. Key words: Pyeloplasty; Pelvic-ureteric junction; Obstructive uropathy; Hydronephrosis; Minimally-invasive surgery; Robotic surgery